Descriptive Study of the Nabawiyah Sirah by Ibn Ishaq and Ibn Hisham - Arditya Prayogi; Alamul Yaqin; M. Zulvi Romzul Huda Fuadi (Sekolah Tinggi Agama Islam Taruna Surabaya, 2022)
The position of sirah or the study of the history of the prophet Muhammad SAW has an important position in the Islamic religious tradition where it ranks second after the study of hadith or sunnah. Thus, this article aims to describe how the study of the nabawiyah sirah was carried out by the two main retainers of its writing, especially seeing how the process and the relationship between these two sirah works from a historical perspective. This article itself was written with a qualitative descriptive approach supported by data collection methods in the form of literature study. From the results of the review, it is known that Ibn Ishaq's sirah is the first work that is able to systematically review the life story of the prophet, although there are still many shortcomings and finally it was perfected by Ibn Hisham with his sirah work. Both Ibn Ishaq and Ibn Hisham, both have important contributions in writing the book Sirah Nabawiyah. Ibn Ishaq with the quality of his book narration is strong enough to make his work an important reference in the study of the nabawiyah sirah.